2023
DOI: 10.2147/copd.s388049
|View full text |Cite
|
Sign up to set email alerts
|

Use of Remote Cardiorespiratory Monitoring is Associated with a Reduction in Hospitalizations for Subjects with COPD

Abstract: Background Chronic obstructive pulmonary disease (COPD) is prevalent and results in high healthcare resource utilization. The largest impact on health status and proportion of healthcare costs in COPD are related to hospitalizations for acute exacerbations. Accordingly, the Centers for Medicare & Medicaid Services have advocated for remote patient monitoring (RPM) to aid in chronic disease management. However, there has been a lack of evidence for the effectiveness of RPM in reducing the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Most recently, Polsky et al ( 44 ) performed a retrospective , non-randomized study on an RPM ‘service’ in patients with COPD which included an undergarment-adhered cardiorespiratory physiologic monitor linked via data capture ‘hub’ to a web-based clinical dashboard. This 2023 study demonstrated that RPM recipients experienced significantly fewer unplanned hospitalizations when compared with usual care.…”
Section: Remote Patient Monitoring and Wearables In Copdmentioning
confidence: 99%
“…Most recently, Polsky et al ( 44 ) performed a retrospective , non-randomized study on an RPM ‘service’ in patients with COPD which included an undergarment-adhered cardiorespiratory physiologic monitor linked via data capture ‘hub’ to a web-based clinical dashboard. This 2023 study demonstrated that RPM recipients experienced significantly fewer unplanned hospitalizations when compared with usual care.…”
Section: Remote Patient Monitoring and Wearables In Copdmentioning
confidence: 99%